The Investigation of Velocity and Temperature Changes by CFD Analysis for Intake Stroke of LPG Fuel Stratified Charge Engine - Can, İbrahim; Öner, Cengiz; Alnak, Dogan Engin; Ozalp, Coskun (My University, 2017)
This study numerically investigates the in-cylinder speed and temperature variations for fuel-air mixture intake at the induction stroke by the LPG cylinder of an engine running on the stratified charge principle. The present study is based on the CFD model created using experimental data. Examinations were performed between the top dead center and the bottom dead center during the induction stroke. Incylinder speed and temperature variations were obtained by k-? turbulence model depending on the crankshaft angle and revolutions per minute (900, 3000, 5500 rpm). The obtained results were compared with the known theoretical values for stratified charge engines, and consistent results were obtained.
Keywords: Mühendislik; Elektrik ve Elektronik